Выражение: (Y^4-Y^2+1)*(Y^2+1)+(Y-1)*(Y+1)
ответ: Y^6+Y^2
Решаем по действиям:
1. (Y^4-Y^2+1)*(Y^2+1)=Y^6+1
(Y^4-Y^2+1)*(Y^2+1)=Y^4*Y^2+Y^4*1-Y^2*Y^2-Y^2*1+1*Y^2+1*1
1.1. Y^4*Y^2=Y^6
Y^4*Y^2=Y^(4+2)
1.1.1. 4+2=6
+4
_2_
6
1.2. Y^2*Y^2=Y^4
Y^2*Y^2=Y^(2+2)
1.2.1. 2+2=4
+2
_2_
4
1.3. Y^4-Y^4=0
1.4. -Y^2+Y^2=0
2. (Y-1)*(Y+1)=Y^2-1
(Y-1)*(Y+1)=Y*Y+Y*1-1*Y-1*1
2.1. Y*Y=Y^2
Y*Y=Y^(1+1)
2.1.1. 1+1=2
+1
_1_
2
2.2. Y-Y=0
3. 1-1=0
-1
_1_
0
Решаем по шагам:
1. Y^6+1+(Y-1)*(Y+1)
1.1. (Y^4-Y^2+1)*(Y^2+1)=Y^6+1
(Y^4-Y^2+1)*(Y^2+1)=Y^4*Y^2+Y^4*1-Y^2*Y^2-Y^2*1+1*Y^2+1*1
1.1.1. Y^4*Y^2=Y^6
Y^4*Y^2=Y^(4+2)
1.1.1.1. 4+2=6
+4
_2_
6
1.1.2. Y^2*Y^2=Y^4
Y^2*Y^2=Y^(2+2)
1.1.2.1. 2+2=4
+2
_2_
4
1.1.3. Y^4-Y^4=0
1.1.4. -Y^2+Y^2=0
2. Y^6+1+Y^2-1
2.1. (Y-1)*(Y+1)=Y^2-1
(Y-1)*(Y+1)=Y*Y+Y*1-1*Y-1*1
2.1.1. Y*Y=Y^2
Y*Y=Y^(1+1)
2.1.1.1. 1+1=2
+1
_1_
2
2.1.2. Y-Y=0
3. Y^6+Y^2
3.1. 1-1=0
-1
_1_
0
Тоесть 2
Выражение: (Y^4-Y^2+1)*(Y^2+1)+(Y-1)*(Y+1)
ответ: Y^6+Y^2
Решаем по действиям:
1. (Y^4-Y^2+1)*(Y^2+1)=Y^6+1
(Y^4-Y^2+1)*(Y^2+1)=Y^4*Y^2+Y^4*1-Y^2*Y^2-Y^2*1+1*Y^2+1*1
1.1. Y^4*Y^2=Y^6
Y^4*Y^2=Y^(4+2)
1.1.1. 4+2=6
+4
_2_
6
1.2. Y^2*Y^2=Y^4
Y^2*Y^2=Y^(2+2)
1.2.1. 2+2=4
+2
_2_
4
1.3. Y^4-Y^4=0
1.4. -Y^2+Y^2=0
2. (Y-1)*(Y+1)=Y^2-1
(Y-1)*(Y+1)=Y*Y+Y*1-1*Y-1*1
2.1. Y*Y=Y^2
Y*Y=Y^(1+1)
2.1.1. 1+1=2
+1
_1_
2
2.2. Y-Y=0
3. 1-1=0
-1
_1_
0
Решаем по шагам:
1. Y^6+1+(Y-1)*(Y+1)
1.1. (Y^4-Y^2+1)*(Y^2+1)=Y^6+1
(Y^4-Y^2+1)*(Y^2+1)=Y^4*Y^2+Y^4*1-Y^2*Y^2-Y^2*1+1*Y^2+1*1
1.1.1. Y^4*Y^2=Y^6
Y^4*Y^2=Y^(4+2)
1.1.1.1. 4+2=6
+4
_2_
6
1.1.2. Y^2*Y^2=Y^4
Y^2*Y^2=Y^(2+2)
1.1.2.1. 2+2=4
+2
_2_
4
1.1.3. Y^4-Y^4=0
1.1.4. -Y^2+Y^2=0
2. Y^6+1+Y^2-1
2.1. (Y-1)*(Y+1)=Y^2-1
(Y-1)*(Y+1)=Y*Y+Y*1-1*Y-1*1
2.1.1. Y*Y=Y^2
Y*Y=Y^(1+1)
2.1.1.1. 1+1=2
+1
_1_
2
2.1.2. Y-Y=0
3. Y^6+Y^2
3.1. 1-1=0
-1
_1_
0
Тоесть 2
4x(4-x)=0 ( Произведение равно нулю, когда хотя бы один из множителей равен нулю)
4x=0 4-x=0
x=0 x=4
ответ : 0; 4
81-x^2=0
(9-x)*(9+x)=0
9-x=0 9+x=0
x=9 x=-9
ответ : -9; 9
x^2+8x-9=0
D=b^2-4ac=64-4*(-9)=100
x1=-8+10/2=1
x2=-8-10/2=-9
ответ : -9; 1